INCLUSIVE DO AND D+ PRODUCTION IN E+E- ANNIHILATION AT 29 GEV - Derrick, M; Fernandez, E; Fries, R; Hyman, L; Kooijman, P; Loos, J; Musgrave, B; Price, L; Schlereth, J; Sugano, K; Weiss, J; Wood, D; et al. (1984)
We have observed inclusive production of D0 and D+ mesons, and their charge conjugates, in e+e- annihilation at 29 GeV on the basis of a data sample of 106 pb-1. These signals correspond to R values of R (D0+D0)=1.8±0.5 and R (D++D-)=1.2±0.4. Taking the D+ and D0 data together, we measure a charge asymmetry of A=-0.08±0.12 for charmed quarks. A comparison of R (D+D) with R (D*+D*) obtained via the process D*+D0+ gives a DD* ratio of 1.0-0.2+0.3, indicating that direct D* production dominates over direct D production. © 1984 The American Physical Society.